Dependency of The Exchange Rate with The Volume of Indonesian Aluminum Exports Using Copula - Kurniadi Rizki; Retno Budiarti; I Gusti Putu Purnaba (Mathematics Department, Maulana Malik Ibrahim State Islamic University of Malang, 2025)
The downstreaming of bauxite, which is one of the raw materials for aluminum, indicates that the Indonesian government is serious about managing these mining resources. As one of the leading commodities, aluminum export activities not only affect investment but also strengthen the IDR-USD exchange rate. The increasing circulation of the rupiah has a positive impact on Indonesia in the international trade market. This study models the dependence between the IDR-USD exchange rate and Indonesia's aluminum export volume using copula. Copula doesn’t require the assumption of data normality, so it is very good for measuring the dependence of economic data that is often not normally distributed. The results of the study concluded that there is a positive correlation between the two variables, although it is not significant and is very small. This positive correlation indicates that the rupiah will strengthen along with the increasing volume of Indonesia's aluminum exports.